Individual differences in scientists’ aesthetic disposition, aesthetic experiences, and aesthetic sensitivity in scientific work - Jacobi, Christopher; Varga, Peter J.; Jessani, Zohaib; Vaidyanathan, Brandon (Frontiers in Psychology, 2024)
Introduction The role of personality in shaping engagement with aesthetics in science has been almost entirely unexplored. Whereas artists and arts settings (e.g., museums) are well-studied from a psychological perspective, the practice of science has often been seen as purely rational or dry. In response, this study presents novel findings on the critical role of scientists’ individual differences, which shape their engagement with aesthetics, such as the frequency of their experiences of beauty, wonder, and awe in their scientific work. Methods Based on a very large and representative four-country study of scientists in the fields of biology and physics (N = 3,092), this study analyzed the associations of Big Five personality traits among scientists with (i) dispositional aesthetics (DPES-awe), (ii) the frequency of aesthetic experiences in scientific work, and (iii) aesthetic sensitivity in science. These survey-weighted OLS regression models included extensive statistical controls for sociodemographic factors. Results As hypothesized, openness is positively, and neuroticism is negatively linked with dispositional aesthetics, the frequency of aesthetic experiences in scientific work, and aesthetic sensitivity in science. Unexpectedly, agreeableness and conscientiousness (but not extraversion) are highly significant and strong predictors of the three trait and state aesthetic engagement variables. Discussion The aesthetic engagement and personality framework of this paper is empirically supported and demonstrates the importance of personality types of scientists in the practice of science. The unexpectedly strong association of agreeableness with aesthetic engagement points to the importance of cooperation, collaboration, and communication to maximize scientific creativity.